STRATEGI PENGEMBANGAN UKM BATU ARCA DI DESA WATESUMPAK DALAM MENGHADAPI ERA GLOBALISASI - ANITA KUSTIARINI (Universitas Negeri Surabaya, 2014)
Watesumpak village is an area that is famous for SMEs stone statues. These SMEs prosper while the 1997 crisis, but in the current era of globalization dwindling due to many problems and obstacles faced by entrepreneurs. This research aims to (1) determine the development strategies of SMEs stone statue in Watesumpak village in the era of globalization, (2) find out the problems faced by SMEs stone statues in the Watesumpak village in the era of globalization, (3) determine the development of SMEs stone statue in the Watesumpak village. This research is a descriptive study with a qualitative approach. The subjects were villagers Watesumpak especially owners stone statues SME as much as 20 informants. Determination of informants using snowball sampling technique. Data analysis consisted of data reduction, data presentation, draw conclusions or verification. The results of this study were (1) a strategy for competitiveness is improve service quality, improve product quality, improve financial management, increase innovation, recruit human resources field appropriate, (2) the obstacles faced by entrepreneurs is the acquisition of raw materials, capital, marketing, marketing, and lack of government support (3) the development of SMEs stone statue in the Watesumpak village is said to decline. Keywords: strategy development SMEs. Desa Watesumpak adalah daerah yang terkenal dengan UKM batu arca. UKM ini berjaya saat krisis 1997, tetapi dalam era globalisasi saat ini jumlahnya semakin berkurang karena banyaknya permasalahan dan hambatan yang dihadapi para pengusaha. Penelitian ini bertujuan untuk (1) mengetahui strategi pengembangan yang digunakan UKM batu arca di desa Watesumpak untuk berdaya saing dalam mengahapi era globalisasi, (2) mengetahui masalah yang dihadapi UKM batu arca di desa Watesumpak dalam era globalisasi, (3) mengetahui perkembangan UKM batu arca di desa Watesumpak. Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kualitatif. Subjek penelitian ini adalah masyarakat desa Watesumpak khususnya pemilik UKM batu arca sebanyak 20 informan. Penentuan informan menggunakan teknik snowball sampling. Analisa data terdiri dari reduksi data, penyajian data, menarik kesimpulan atau verifikasi. Hasil penelitian ini adalah (1) strategi untuk berdaya saing adalah meningkatkan kualitas pelayanan, meningkatkan kualitas produk, memperbaiki manajemen keuangan, meningkatkan inovasi, merekrut SDM sesuai bidangnya, (2) hambatan yang dihadapi para pengusaha adalah perolehan bahan baku, permodalan, pemasaran, pemasaran, dan kurangnya dukungan pemerintah (3) perkembangan UKM batu arca di desa Watesumpak dikatakan menurun. Kata kunci : Strategi pengembangan UKM